2014
DOI: 10.1016/j.annals.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Is the migration-tourism relationship only about VFR?

Abstract: This paper contributes to the literature on the linkages between tourism and migration. Though it is widely recognised that the two phenomena are closely linked, and that migration may induce VFR (visiting friends and relatives) tourism, there has been little econometric evaluation of the relationship. The present analysis draws upon Australian data to identify a strong quantitative link between migration and VFR tourism. It also demonstrates a strong link between migration and other forms of tourism. Indeed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 21 publications
5
71
0
Order By: Relevance
“…Seetaram (2012) argued that immigration can act as a catalyst for international tourism flow and that immigrants who retain or forge business links with their origin country may stimulate business travel. Dwyer et al (2014) has confirmed that there is a strong relationship between migration and the tourism associated with visiting friends and relatives. Therefore, an immigration dummy (IMMI) that captures the top 10 countries of birth for Australia's overseas-born population is included.…”
Section: Methodology and Datasupporting
confidence: 76%
“…Seetaram (2012) argued that immigration can act as a catalyst for international tourism flow and that immigrants who retain or forge business links with their origin country may stimulate business travel. Dwyer et al (2014) has confirmed that there is a strong relationship between migration and the tourism associated with visiting friends and relatives. Therefore, an immigration dummy (IMMI) that captures the top 10 countries of birth for Australia's overseas-born population is included.…”
Section: Methodology and Datasupporting
confidence: 76%
“…Some have argued that VFR travel could also be synonymous with ethnic tourism. Migrants often visit their communities of origin with mixed motivations to see people, culture, and places (Duval, ; Dwyer et al, ; Pearce & Moscardo, ), indicating a strong relationship between migration and subsequent travel patterns (Hughes & Allen ; King, ; King & Gammage, ). Pearce () introduced the term visiting home and familiar places (VHFP), travel that “focuses on the places and relationships entangled in… [travellers'] personal and historical biographies” (p. 1027).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is a robust technique which is widely used in the tourism context and ensures that results obtained are reliable (Seetaram, 2010(Seetaram, , 2012aSeetaram and Petit, 2012). As yet, competitiveness indices have not been widely used as a price variable in tourism demand analysis, though they are beginning to be used (see, Athanasopoulos et al, 2014;Dwyer et al, 2014, Forsyth et al 2012and Etzo et al, 2014. To illustrate the superiority of PCI over the REX, the model is estimated using each separately as the proxy for prices.…”
Section: Objections To Using Rexmentioning
confidence: 99%